2020
DOI: 10.7717/peerj.8760
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of the velocity achieved during the last repetition of sets to failure and its association with the velocity of the 1-repetition maximum

Abstract: Background: This study aimed to determine the reliability of the velocity achieved during the last repetition of sets to failure (V last ) and the association of V last with the velocity of the 1-repetition maximum (V 1RM ) during the paused and touch-and-go bench press (BP) exercises performed in a Smith machine. Methods: A total of 96 healthy men participated in this study that consisted of two testing sessions. A single BP variant (paused BP or touch-and-go BP) was evaluated on each session in a randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…Therefore, the daily training load can be matched to the previously programmed intensity, since it is acknowledged that each %1RM corresponds to a specific mean concentric velocity. This finding has been reported and used in several studies that achieved similar results, although some studies propose individualizing the load-velocity relationship for each subject ( González-Badillo & Sánchez-Medina, 2010 ; Sánchez-Medina et al, 2017 ; García-Ramos et al, 2019 ; García-Ramos & Janicijevic, 2020 ). In this sense, VBT differs from traditional approaches by modifying training load variables to match the pre-programmed ones prior to a given training session, rather than assigning them based on a 1RM pre-test.…”
Section: Introductionsupporting
confidence: 74%
“…Therefore, the daily training load can be matched to the previously programmed intensity, since it is acknowledged that each %1RM corresponds to a specific mean concentric velocity. This finding has been reported and used in several studies that achieved similar results, although some studies propose individualizing the load-velocity relationship for each subject ( González-Badillo & Sánchez-Medina, 2010 ; Sánchez-Medina et al, 2017 ; García-Ramos et al, 2019 ; García-Ramos & Janicijevic, 2020 ). In this sense, VBT differs from traditional approaches by modifying training load variables to match the pre-programmed ones prior to a given training session, rather than assigning them based on a 1RM pre-test.…”
Section: Introductionsupporting
confidence: 74%
“…Of these three devices, the Push 2.0 may have the greatest accuracy. However, it should be acknowledged that mean velocity from this device has been questioned [29], which limits its application to resistance training as this metric is widely recommended for use during non-ballistic exercises [12,64,65]. Finally, of the non-linear transducer and accelerometer devices, it appears that smart phone and tablet apps may be an alternative for a quick 'snap-shot' of training intensity, but substantial inter-device error may exist.…”
Section: Resultsmentioning
confidence: 99%
“…To circumvent these issues and support the accurate quantification of resistance training loads, a range of tools that assess kinetic and kinematic outputs have been developed [8][9][10][11]. By monitoring kinetic and kinematic outputs, changes in fatigue and proximity to concentric muscle failure can be closely monitored [6,12,13]. Furthermore, these devices have been used for a number of training purposes ranging from the immediate feedback of velocity and power outputs [14][15][16][17], to supporting full autoregulatory prescriptive methods [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…A possible solution for basketball researchers and practitioners to gather strength data from their players is to use a linear position transducer (LPT) during resistance training sessions to measure kinetic and kinematic outputs [36,171]. The use of an LPT during strength training can provide valid and reliable performance data [172], which is able to be tracked over time to monitor player progression (e.g., changes in bar speed at a specified load) [171,173], and used to predict maximal strength whilst inducing minimal fatigue [171,174,175]. Only one study [121] reported bench press 1RM relative to playing position in adult male basketball players.…”
Section: Strengthmentioning
confidence: 99%